2017
DOI: 10.1002/btm2.10065
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cell culture parameters on production and vascularization bioactivity of mesenchymal stem cell‐derived extracellular vesicles

Abstract: Mesenchymal stem cell (MSC)‐derived extracellular vesicles (EVs) have emerged as potential therapeutic agents for numerous applications. EVs offer potential advantages over cell‐based therapies with regard to safety, stability and clearance profiles, however production and potency limitations must be addressed to enable eventual translation of EV‐based approaches. Thus, we sought to examine the role of specific cell culture parameters on MSC EV production and bioactivity toward informing rational design parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
148
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 172 publications
(160 citation statements)
references
References 50 publications
7
148
3
2
Order By: Relevance
“…Previous reports have shown that increasing hMSC passage number decreases the invasiveness and bioactivity of hMSCs (Patel et al, ; Spagnol et al, ), so we investigated hMSC speed as a function of passage and of confinement. hMSCs at passage 3, 4, or 5 (P3, P4, or P5) were seeded in the microfluidic device, and the speed of hMSCs migrating within microchannels was subsequently tracked.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that increasing hMSC passage number decreases the invasiveness and bioactivity of hMSCs (Patel et al, ; Spagnol et al, ), so we investigated hMSC speed as a function of passage and of confinement. hMSCs at passage 3, 4, or 5 (P3, P4, or P5) were seeded in the microfluidic device, and the speed of hMSCs migrating within microchannels was subsequently tracked.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have indicated that hMSC behavior can be passage dependent, as increased passage leads to loss of hMSC proliferative capacity and multipotency (Banfi et al, ), and also reduced exosome production and invasiveness (Patel et al, ; Spagnol et al, ). Therefore, we hypothesized that passage number would influence hMSC migration, possibly as a function of confinement.…”
Section: Discussionmentioning
confidence: 99%
“…Low-density inoculation (1.5 cells/cm 2 ) may result in faster stem cell proliferation [84]. Low-density cultures may activate EV-mediated paracrine signaling of stem cells and promote EV secretion [85].…”
Section: Cell Densitymentioning
confidence: 99%
“…Stem cells alter phenotypes and functions as the in vitro expansion time increases. Early MSCs have the potential for osteogenic and adipogenic differentiation, and the differentiation potential tilts toward adipogenesis as the in vitro culture is extended [85]. MSCs secrete less EVs after aging [85].…”
Section: Cell Phenotypesmentioning
confidence: 99%
“…In terms of scientific topics, BioTM has focused on subjects where Engineering, Chemical Engineering in particular, has made a strong fundamental and translational impact on the field. These topics include drug delivery, Nucleic acid delivery, Regenerative Medicine, Biotechnology, Nanomedicine, Biomedical Devices, and immunotherapy . We look forward to continue building our strengths in these fields and expand the list to include additional key areas.…”
mentioning
confidence: 99%